Usage of Traditional and Complementary Medicine (T & CM): Prevalence, Practice and Perception among Post Stroke Patients Attending Conventional Stroke Rehabilitation in A Teaching Hospital in Malaysia - Mohd Fairuz Ali; Aznida Firzah Abdul Aziz; Zuraidah Che Man; Amnor Aidiliana Amir; Lim Yinn Shien; Nurul Shahida Ramli; Nur Asilah Anez Zainal Abidin; Mohd Radzniwan A Rashid (Malaysian Medical Association, 2024)
Indexed by Scopus